The day of the bomb - Bruckner, Karl, 1906- (London : Burke Books, 1963)
The effects of war on Japan and the world are seen through the experiences of one family that survived the bombing of Hiroshima.
Translation of Sadako will leben.
engund
Keywords: World war, 1939-1945 -- Fiction; Atomic bomb -- Fiction; Hiroshima- shi (Japan) -- History -- Bombardment, 1945 -- Juvenile fiction; Hiroshima- shi (Japan) -- History -- Bombardment, 1945 -- Fiction